The use of angiotensin system inhibitors correlates with longer survival in resected pancreatic adenocarcinoma patients. Issue 3 (March 2023) - Liu, Hao; Nassour, Ibrahim; Lebowitz, Steven; D'Alesio, Mark; Hampton, Erica; Desilva, Annissa; Hammad, Abdulrahman; AlMasri, Samer; Khachfe, Hussein H.; Singhi, Aatur; Bahary, Nathan; Lee, Kenneth; et al.
Abstract: Background: Activities and inhibition of the Renin-Angiotensin-Aldosterone System (RAAS) may affect the survival of resected pancreatic ductal adenocarcinoma (PDAC) patients Method: A single-institution retrospective analysis of resected PDAC patients between 2010 and 2019. To estimate the effect of angiotensin system inhibitors (ASIs) on patient survival, we performed Kaplan Meier analysis, Cox Proportional Hazards model, Propensity Score Matching (PSM), and inverse probability weighting (IPW) analysis. Results: 742 patients were included in the analysis. The average age was 67.0 years, with a median follow-up of 24.1 months. The use of ASI was associated with significantly longer overall survival in univariate (p = 0.004) and multivariable (HR = 0.70 [0.56–0.88], p = 0.003) adjusted analysis. In a propensity score-matched cohort of 400 patients, ASI use was again associated with longer overall survival (p = 0.039). Lastly, inverse probability weighting (IPW) analysis suggested that the use of ASI was associated with an average treatment effect on the treated (ATT) of HR = 0.68 [0.53–0.86], p = 0.002) for overall survival. Conclusion: In this single-institution retrospective study focusing on resected PDAC patients, the use of ASI was associated with longer overall survival in multiple statistical models. Prospective clinical trials are needed before routine clinical implementation of ASI as an adjuvant to existing therapy can be recommended.